Reusable and highly sensitive SERS immunoassay utilizing gold nanostars and a cellulose hydrogel-based platform - Oliveira, Maria João (2022)
This work was funded by FEDER funds through the COMPETE 2020 Programme and National Funds through the FCT---Fun-dação para a Ciência e a Tecnologia, I. P., under the scope of the project. This work also received funding from the European Community’s H2020 program under grant agreement No. 716510 (ERC-2016-STG TREND), 640598 (ERC-StG-2014, NEWFUN), and 685758 (1D-Neon). This work was supported by the Applied Molecular Biosciences Unit – UCIBIO and Associate Laboratory for Green Chemistry – LAQV which are financed by Portugal national funds from /2016 and SFRH/BD/132057/2017 from the FCT/MCTES and MIT Portugal PhD Program (to I. C. and M. J. O., respectively). Professor César Laia (LAQV-REQUIMTE, Faculdade de Ciências e Tecnologia, Universidade NOVA de Lisboa, Portugal) is acknowledged for permitting the use of DLS equipment. Professor Ludwig Krippahl (NOVA LINCS, Faculdade de Ciências e Tecnologia, Universidade NOVA de Lisboa, Portugal) is acknowledged for developing the gel analysis application eReuss. M. J. O. acknowledges Rocío Palomares Jurado PhD for visualisation/data presentation support and continued interest in the project. M. J. O. acknowledges David Peitinho MSc for help and advice in Python script. Diego Wiechers de Carvalho BSc is acknowledged for purifying the recombinant Plasmodium falciparum histidine-rich protein 2 sample and Daniela Gomes PhD for providing SEM images. Publisher Copyright: © The Royal Society of Chemistry 2021.